Comparison of the association between different ozone indicators and daily respiratory hospitalization in Guangzhou, China - Lin, Geng; Wang, Zhuoqing; Zhang, Xiangxue; Stein, Alfred; Maji, Kamal Jyoti; Cheng, Changxiu; Osei, Frank; Yang, Fiona Fan (Frontiers in Public Health, 2023)
Background: Epidemiological studies have widely proofed the impact of ozone (O3) on respiratory mortality, while only a few studies compared the association between different O3 indicators and health. Methods: This paper explores the relationship between daily respiratory hospitalization and multiple ozone indicators in Guangzhou, China, from 2014 to 2018. It uses a time-stratified case-crossover design. Sensitivities of different age and gender groups were analyzed for the whole year, the warm and the cold periods. We compared the results from the single-day lag model and the moving average lag model. Results: The results showed that the maximum daily 8h average ozone concentration (MDA8 O3) had a significant effect on the daily respiratory hospitalization. This effect was stronger than for the maximum daily 1h average ozone concentration (MDA1 O3). Results further showed that O3 was positively associated with daily respiratory hospitalization in the warm season, while there was a significantly negative association in the cold season. Specifically, in the warm season, O3 has the most significant effect at lag 4 day, with the odds ratio (OR) equal to 1.0096 (95% confidence intervals (CI): 1.0032, 1.0161). Moreover, at the lag 5 day, the effect of O3 on 15-60 yr-old age group was less than that on people over 60 yr-old, with the OR value of 1.0135 (95% CI: 1.0041, 1.0231) for 60+ age group; female was more sensitive than male to O3 exposure, with an OR value equal to 1.0094 (95% CI: 0.9992, 1.0196) for female group. Conclusion: These results show that different O3 indicators measure different impacts on the respiratory hospitalization admission. Their comparative analysis provided a more comprehensive insight into exploring associations between O3 exposure and respiratory health.